SECOND DERIVATIVE SPECTROPHOTOMETRIC METHOD FOR SIMULTANEOUS DETERMINATION OF DOXYLAMINE SUCCINATE AND PYRIDOXINE HCL IN PHARMACEUTICAL FORMULATIONS: Pharmaceutical Science-Analytical Chemistry - KUMAR KASTURI, AMAR; RAJU MEDICHERLA, KANAKA; YAGANTI, RAGHUVEER; N. BALAKRISHNAN (International Journal of Life Science and Pharma Research, 2019)
Estimation of drugs in pharmaceutical formulations by using UV-Visible spectrophotometric method is one of the most frequently used techniques in pharmaceutical analysis. Simple and reliable second derivative spectrophotometric method was developed and validated for the simultaneous estimation of Doxylamine Succinate and Pyridoxine HCL in bulk and pharmaceutical formulations. The quantitative determination of the drugs was carried out using the second derivative values measured at 239 nm and 290 nm for Doxylamine Succinate and Pyridoxine Hcl respectively. The method has been developed and validated for the assay of Doxylamine Succinate and Pyridoxine HCL using methanol as diluents. Calibration graphs drawn at their wavelengths of determination were linear in the concentration range of 1-8 µg mL-1 for Doxylamine Succinate and 12.5 - 100 µg mL-1 for Pyridoxine Hcl. At 232 nm Doxylamine Succinate showed zero absorbance but Pyridoxine HCL had considerable amount of absorbance. Similarly at 290 nm Pyridoxine HCL showed zero absorbance but Doxylamine Succinate had considerable amount of absorbance. The limit of Quantification (LOQ) of Doxylamine Succinate and Pyridoxine HCL was found to be 0.6 µg mL-1 and 1µg mL-1 respectively and the limit of detection (LOD) was found to be 0.08 µg mL-1 and 0.3 µg mL-1 respectively. Comparison second derivative spectrum of Doxylamine Succinate and Pyridoxine HCL in standard and drug formulation solutions showed that the wavelength of maximum absorbance did not change. The low relative standard deviation values indicate good precision and high recovery values indicate accuracy of the proposed method. Developed second derivative spectrophotometric method was simple, accurate, precise, specific, sensitive and reproducible, which can be directly and easily applied to pharmaceutical dosage forms.